Ultrasound elastography: a brief clinical history of an evolving technique - Dietrich, Christoph F.; Dong, Yi; Cui, Xin-Wu; Fink, Mathias; Jenssen, Christian; Moeller, Kathleen; Sandrin, Laurent; Tsuneyoshi, Sugimoto; Tanter, Mickael (Ultrasound International Open, 2024)
The history of the emerging elastographic technique is presented. Ultrasound imaging of elasticity and tissue strain has gained clinical acceptance as an established technique useful in routine daily clinical practice.
Keywords: ultrasound; elastography; history